In Vitro Assays for the Assessment of Safety and Toxicity in Pharmacopuncture Derived from Animal - Yu-Jin So; Hyein Jeong; Kyeong Han Kim; Seong-Gyu Ko (Journal of Pharmacopuncture)
Objectives: Among the various treatment methods involving the use of natural substances, pharmacopuncture using animal venom is a relatively new form of acupuncture that has been developed in South Korea and is gaining popularity worldwide. Pharmacopuncture with animal venom is widely used in clinical practice; therefore, ensuring its procedural safety is crucial. This study aimed to evaluate the safety and toxicity of pharmacopuncture using animal venom.Methods: In October 2021, nine samples of animal venom-derived pharmacopuncture products were randomly collected from four External Herbal Dispensaries (EHDs). These samples underwent sterility and microbial limit testing to ensure they were free from microbial contamination. Toxicity tests were conducted using three different cell lines to evaluate cytotoxic effects.Results: The sterility and microbial limit tests showed no microbial growth in any of the pharmacopuncture samples. However, the toxicity tests revealed that bee venom exhibited strong cytotoxicity. Furthermore, samples containing Bovis Calculus, Fel Ursi, and Moschus also demonstrated varying degrees of cytotoxic effects.Conclusion: This study is the first to analyze the safety and toxicity of animal venomderived pharmacopuncture products, providing evidence for its procedural safety. Although the samples analyzed were limited to four EHDs, these findings highlight the importance of further research on the safety and toxicity of pharmacopuncture to ensure its clinical application is both effective and safe.